A buffer management algorithm based on message grouping - Wang, Hezhe; Wang, Huiqiang (Discover applied sciences, 2025)
In the opportunity network, effective buffer management methods are important means to improve network performance when buffer overflow. Therefore, this article proposes a message grouping based opportunistic network buffer management method. This method first determines the relationship between the buffer space required to receive all messages in the message set and the size of the idle buffer of the node. If the idle buffer of the node is not less than the buffer space occupied by the message set to be received, all messages to be received are received. Otherwise, the number of messages in the message set to be received is further determined, and which messages in the node buffer to discard are selected based on the number of messages in the message set to be received, thereby alleviating the problem of buffer overflow. The simulation results show that the algorithm proposed in this paper outperforms Drop Oldest algorithm and Drop Largest algorithm in terms of delivery ratio, delay and network overhead. Article highlights This article proposes a message grouping principle that groups the original messages in a node. When the node buffer overflows, the message is selected from the group of messages to be received for discarding. This article proposes three methods for discarding messages. In the process of discarding messages, this article will choose the corresponding message discarding method based on the number and size of the messages to be received. This article proposes a buffer management algorithm, which considers multiple network attributes and the maximum number of discarded messages.